Типологія додатків у сучасних лінгвістичних словниках - Гордієнко, Н. (Лексикографічний бюлетень, 2012)
У статті проаналізовано найхарактерніші особливості додатків для словників лінгвістичного типу, класифікуємо їх, а також спробуємо подати типологію додаткового матеріалу. This article analyses the role of the outside matter in the structure of modern linguistic dictionaries, describes its characteristic features and suggests some typology. It shows that appendices have become more common and more informative in the XXI century dictionaries. Such changes account for updating the format of dictionaries, developing and improving their structure.